Anionic Indicators on the Surface of Submicrospheres Consisting of Ionic Palladium(II) Complex - Kim, Cho Rong; Noh, Tae Hwan; Yoo, Kyung Ho; Yoo, Bok Ryul; Jung, Ok-Sang (WILEY-V C H VERLAG GMBH, 2009)
Ionic palladium(II) complex, [(Me(4)en)Pd(L)](2)(ClO4)(4) (Me(4)en = N,N,N',N'-tetramethylethylenediamine; L = bis-(4-(4-pyridylcarboxyl)phenyl)methane), allows to form a monodisperse submicrosphere without any template or additive. Surface-perchlorates on the submicrosphere have been exchanged by anionic pH indicators such as thymol blue, bromothymol blue, and bromocresol green. The ionic and amphiphilic properties of the palladium(II) complex appear to be primarily associated with the Formation and easy surface-anion exchange of submicrosphere. The surface-anion exchange through the electrostatic interaction is a very good tool for the surface-modification. The color of the pH indicator-exchanged submicrospheres is very sensitive to pH and Hg2+ cation, and thus they are promising to submicrospherical indicators.
Keywords: NANOPARTICLES; ARRAYS